Prognostic utility of serum YKL-40 in patients with cervical cancer. (1st December 2020) - Roslind, Anne; Palle, Connie; Johansen, Julia Sidenius; Christensen, Ib Jarle; Nielsen, Hans Jørgen; Mosgaard, Berit Jul
Abstract: Inflammation is one of the hallmarks of cancer and plays a crucial role in the development and progression. The objective of the present study was to investigate if high serum YKL-40 is related to poor prognosis in cervical cancer (CC) patients. A prospective biomarker study of 116 patients with CC (FIGO stage Ia: n = 4; Ib: n = 55; II: n = 26; III: n = 26; IV: n = 5) and 152 patients with cervical intraepithelial neoplasia (CIN). The patients received primary surgery, radiotherapy and chemotherapy according to standard guidelines during the period 2001–2004. Seventy patients died during the follow-up period (median 117 months, range 104–131). Serum concentrations of YKL-40 were measured by ELISA. Serum concentrations of YKL-40 were increased ( p < .001) in CC patients (median 76 µg/L, IQR 45–148) compared to CIN patients (44 µg/L, IQR 30–61) and healthy women (41 µg/L, IQR 29–58). YKL-40 was elevated (>age-corrected 95th percentile of YKL-40 in healthy women) in 30 (26%) of the CC patients. Univariate Cox analysis demonstrated that YKL-40 (included as a log-transformed continuous variable (base 2)) was associated with recurrence-free survival (RFS) (HR = 1.48, 95% CI: 1.11–1.98, p = .008) and overall survival (OS) (HR = 1.74, 1.44–2.10, p < .0001). Multivariate Cox analysis showed that stage (II + III vs. I: HR = 2.92, 1.37–6.20, p = .005), YKL-40 (HR = 1.35, 1.06–1.73, p = .018) and age (HR = 1.56, 1.21–1.99, p = .0005) were independent prognostic variables of OS. During treatment, a 2-fold increase in YKL-40 compared to baseline level was associated with short RFS (HR = 1.87, 1.27–2.77, p = .0016) and OS (HR = 1.78, 1.26–2.50, p = .0010). Serum YKL-40 is an independent biomarker of OS in patients with cervical cancer.